Kandungan Neutral Detergent Fibre (NDF) dan Acid Detergent Fibre (ADF) Bahan Pakan Lokal Ternak Sapi yang Dipelihara pada Kandang Kelompok - Suhubdy Suhubdy; Sofyan Damrah Hasan; Syamsul Hidayat Dilaga; I Wayan Karda; Sudirman Sudirman (Faculty of Animal Husbandry, University of Mataram, 2015)
A research had been conducted in order to determine the Neutral Detergent Fiber (NDF) and Acid Detergent Fiber (ADF) of local forages given to 20 cattle raised in communal stalls/cages of â€œBatu Ngompalâ€, West Lombok Regency. Sampling was taken hierarchically. First, forage samples were collected from each feedbag containing 30-kg forages. Every bag was sampled 6-kg for determining their botanical composition. The total botanical sample bags were 120. The forage varieties identified from each bag were pooled and ranked to be 28 dominant kinds of forages. The second determination was conducted for analyzing the cell wall (ADF and NDF) contents from the total botanical composition of forages indentified. The results showed that the contents of NDF and ADF were 51.76 Â± 15.18 % and 35.95 Â± 10.38 %, respectively. The forages ADF contents were then converted to be energy in terms of net energy maintenance (NEm, Mcal/kg), net energy gain (NEg, Mcal/kg), and Total Digestible Nutrients (TDN, %) with the results of 0.59 Mcal/kg, 0.31 Mcal/kg, and 58.74 %, respectively.